Combination of prostate imaging reporting and data system (PI‐RADS) score and prostate‐specific antigen (PSA) density predicts biopsy outcome in prostate biopsy naïve patients. (1st April 2016) - Washino, Satoshi; Okochi, Tomohisa; Saito, Kimitoshi; Konishi, Tsuzumi; Hirai, Masaru; Kobayashi, Yutaka; Miyagawa, Tomoaki
Abstract : Objective: To assess the value of the Prostate Imaging Reporting and Data System (PI‐RADS) scoring system, for prostate multi‐parametric magnetic resonance imaging (mpMRI) to detect prostate cancer, and classical parameters, such as prostate‐specific antigen (PSA) level, prostate volume and PSA density, for predicting biopsy outcome in biopsy naïve patients who have suspected prostate cancer. Patients and methods: Patients who underwent mpMRI at our hospital, and who had their first prostate biopsy between July 2010 and April 2014, were analysed retrospectively. The prostate biopsies were taken transperineally under transrectal ultrasonography guidance. In all, 14 cores were biopsied as a systematic biopsy in all patients. Two cognitive fusion‐targeted biopsy cores were added for each lesion in patients who had suspicious or equivocal lesions on mpMRI. The PI‐RADS scoring system version 2.0 (PI‐RADS v2) was used to describe the MRI findings. Univariate and multivariate analyses were performed to determine significant predictors of prostate cancer and clinically significant prostate cancer. Results: In all, 288 patients were analysed. The median patient age, PSA level, prostate volume and PSA density were 69 years, 7.5 ng/mL, 28.7 mL, and 0.26 ng/mL/mL, respectively. The biopsy results were benign, clinically insignificant, and clinically significant prostate cancer in 129 (45%), 18 (6%) and 141 (49%) patients, respectively. The multivariate analysis revealed that PI‐RADS v2 score and PSA density were independent predictors for prostate cancer and clinically significant prostate cancer. When PI‐RADS v2 score and PSA density were combined, a PI‐RADS v2 score of ≥4 and PSA density ≥0.15 ng/mL/mL, or PI‐RADS v2 score of 3 and PSA density of ≥0.30 ng/mL/mL, was associated with the highest clinically significant prostate cancer detection rates (76–97%) on the first biopsy. Of the patients in this group with negative biopsy results, 22% were subsequently diagnosed as prostate cancer. In contrast, a PI‐RADS v2 score of ≤3 and PSA density of <0.15 ng/mL/mL yielded no clinically significant prostate cancer and no additional detection of prostate cancer on further biopsies. Conclusions: A combination of PI‐RADS v2 score and PSA density can help in the decision‐making process before prostate biopsy and in the follow‐up strategy in biopsy naïve patients. Patients with a PI‐RADS v2 score of ≤3 and PSA density of <0.15 ng/mL/mL may avoid unnecessary biopsies.